2020
DOI: 10.1016/j.plefa.2020.102174
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes, a potential target for Covid-19

Abstract: Repositioning of clinically approved drugs that may reduce the severity, hospitalization events, and time of recovery from SARS-CoV2 infection is a global health priority. Clinical reports of drug effects and lung pathology are providing insight into the pathogenesis of Covid-19, and comparison of these findings with our knowledge of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) can be used to develop rational hypotheses to prioritize clinical studies of available therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…41 Six articles (16.7%) proposed MK as a potential treatment in SARS-CoV-2 positive patients through altering NF-kB signaling pathway, targeting the increased vascular permeability, suppressing recruitment of the innate immune response as well as bronchoconstriction resulted from cytokine release and also lung injury. 14,15,[29][30][31]43 MK was evaluated as the only applied medicine in four out of six surveys. [29][30][31]43 However, the combination of MK with zileuton controlled-release (CR) in one study and MK with levocetirizine in another survey was suggested to be beneficial in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Six articles (16.7%) proposed MK as a potential treatment in SARS-CoV-2 positive patients through altering NF-kB signaling pathway, targeting the increased vascular permeability, suppressing recruitment of the innate immune response as well as bronchoconstriction resulted from cytokine release and also lung injury. 14,15,[29][30][31]43 MK was evaluated as the only applied medicine in four out of six surveys. [29][30][31]43 However, the combination of MK with zileuton controlled-release (CR) in one study and MK with levocetirizine in another survey was suggested to be beneficial in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…14,15,[29][30][31]43 MK was evaluated as the only applied medicine in four out of six surveys. [29][30][31]43 However, the combination of MK with zileuton controlled-release (CR) in one study and MK with levocetirizine in another survey was suggested to be beneficial in COVID-19 patients. 14,15 Eighteen studies (50%) involved confirmed SARS-CoV-2 positive patients (Table 2) comprising two studies that detected high levels of leukotrienes (LTs) in the sera from COVID-19 patients, 44,45 indicating a therapeutic role for MK as an effective leukotriene inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…It was pointed out as a possible SARS-CoV-2 M pro inhibitor in a molecular-docking virtual screening 33 and as an adjuvant treatment promotes the recovery of all types of COVID-19 and further reduces the mortality rate of elderly and those with comorbidities in a clinical study 34 . The NSAID fenoprofen calcium inhibits both isozymes of COX and activates both peroxisome proliferator activated receptors 35 ; therefore, it may downregulate leukotriene B4 production and thereby interfere with the leukotriene pathway of inflammatory exacerbation, which has been demonstrated to mediate lung injury in several diseases [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of SARS-CoV-2 infection, leukotrienes are not paid attention to (Funk and Ardakani 2020 ). Since leukotriene inhibitors are used in anti-cancer treatments (Steele et al 1999 ; Werz and Steinhillber 2006 ), they are also suggested for COVID-19 patients (Citron et al 2020 ; Funk and Ardakani 2020 ). However, it has been recommended that ACE inhibitors in combination with NSAIDs increase the risk of kidney injury, yet, sufficient scientific evidence has not been established for this (Zolk et al 2020 ).…”
Section: Inflammation and Painmentioning
confidence: 99%